ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN SEBELUM DAN KETIKA PADEMI COVID-19 PT SEMEN INDONESIA (PERSERO) Tbk PERIODE 2017-2021 - Benny Osta Nababan; Muhlis Muhlis; Zeze Zakaria Hamzah; Anisa Choerunisa (Institut Teknologi dan Bisnis Dewantara, 2023)
This study aims to measure the ability of financial performance at PT Semen Indonesia (PERSERO) Tbk. before and during the Covid-19 pandemic Period 2017 – 2021 This research uses a type of comparative research with a quantitative approach, which is research that has the nature of comparing data to see similarities and differences in some facts and the nature of the object of research based on a framework of thought. This study uses secondary data obtained from company financial reports accessed through the IDX. The results of the study indicate that the liquidity ratio (current ratio, quick ratio and cash ratio), solvency ratio (total debt to total asset ratio, total debt to total equity ratio, long term debt to equity ratio), activity ratios (inventory turnover, fixed asset turnover, total asset turnover), profitability ratios (net profit margin, return on investment, return one equity) and market ratio (earning per share and price earning ratio). From this research, the company's financial performance has decreased compared to before and during Covid-19.